Permasalahan sampah: Pengelolaan sampah di Indonesia - Azizah, Yunifa (Maliki Interdisciplinary Journal, 2024)
Waste management is a major problem in progress, especially the waste problem in urban areas. The purpose of this article is to under stand waste management in Indonesia with several supporting factors. Because public awareness and supervision from the government is needed in waste management in Indonesia which continues to increase every year. The method used in this article is a system of observing or observing data contained in several journal and news. Seeing the many waste problems in Indonesia that have no solution, it is hoped that this article will support public awareness in dealing with waste. Waste management is the collection, utilization and destruction of waste. Good waste management with 3R, namely Reduce, Recycle, and Reuse.